Development and exergoeconomic evaluation of a SOFC-GT driven multi-generation system to supply residential demands: Electricity, fresh water and hydrogen. (17th May 2021) - Chitgar, Nazanin; Emadi, Mohammad Ali
Abstract: In this study, a novel multi-generation system is proposed by integrating a solid oxide fuel cell (SOFC)-gas turbine (GT) with multi-effect desalination (MED), organic flash cycle (OFC) and polymer electrolyte membrane electrolyzer (PEME) for simultaneous production of electricity, fresh water and hydrogen. A comprehensive exergoeconomic analysis and optimization are conducted to find the best design parameters considering exergy efficiency and total unit cost of products as objective functions. The results show that the exergy efficiency and the total unit cost of products in the optimal condition are 59.4% and 23.6 $/GJ, respectively, which offers an increase of 2% compared to exergy efficiency of SOFC-GT system. Moreover, the system is capable of producing 2.5 MW of electricity by the SOFC-GT system, 5.6 m 3 /h of fresh water by MED unit, and 1.8 kg/h of hydrogen by the PEME. The associated cost for producing electricity, fresh water and hydrogen are 3.4 cent/kWh, 37.8 cent/m 3, and 1.7 $/kg, respectively. A comparison between the results of the proposed system and those reported in other related papers are presented. The diagram of the exergy flow is also plotted for the exact determination of the exergy flow rate in each component, and also, location and value of exergy destruction. Finally, the capability of the proposed system for a case study of Iran is examined. Highlights: A SOFC-based multigeneration system with MED unit and PEME is proposed. Thermodynamic and exergoeconomic analyses are performed. The optimal design parameters are obtained by multi-objective optimization. The exergy efficiency and total unit cost of products are 59.4% and of 23.6 $/GJ. The system produces 2.5 MW electricity, 5.6 m 3 /hr water and 1.8 kg/hr hydrogen.